Prevalence and prescribing patterns of oral corticosteroids in the United States, Taiwan, and Denmark, 2009-2018 - Beth I. Wallace; Hui‐Ju Tsai; Paul Lin; Kristian Aasbjerg; Ann Chen Wu; Yi‐Fen Tsai; Christian Torp‐Pedersen; Akbar K. Waljee; Tsung‐Chieh Yao (Wiley, 2023)
Abstract Oral corticosteroids (OCS) are commonly prescribed for acute, self‐limited conditions, despite studies demonstrating toxicity. Studies evaluating longitudinal OCS prescribing in the general population are scarce and do not compare use across countries. This study investigated and compared OCS prescription patterns from 2009 to 2018 in the general populations of the United States, Taiwan, and Denmark. This international population‐based longitudinal cohort study used nationwide claims databases (United States: Optum Clinformatics Data Mart; de‐identified; Taiwan: National Health Insurance Research Database; and Denmark: National Prescription and Patient Registries/Danish National Patient Registry) to evaluate OCS prescribing. We classified annual OCS duration as short‐term (1-29 days), medium‐term (30-89 days), or long‐term (≥90 days). Longitudinal change in annual prevalence of OCS use and physician prescribing patterns were reported. Among 54,630,437 participants, average annual percentage of overall OCS use was 6.8% in the United States, 17.5% in Taiwan, and 2.2% in Denmark during 2009-2018. Prevalence of OCS prescribing increased at an average annual rate of 0.1%-0.17%, mainly driven by short‐term prescribing to healthy adults. One‐quarter to one‐fifth of OCS prescribing was associated with a diagnosis of respiratory infection. Family practice and internal medicine physicians were among the highest OCS prescribers across countries and durations. Age‐ and sex‐stratified trends mirrored unstratified trends. This study provides real‐world evidence of an ongoing steady increase in OCS use in the general populations of the United States, Taiwan, and Denmark. This increase is largely driven by short‐term OCS prescribing to healthy adults, a practice previously viewed as safe but recently shown to incur substantial population‐level risk.